Spall fracture forms of high rock samples under uniaxial compression - Vasyliev, Leonid; Bulich, Yurii; Vasyliev, Dmytro; Malich, Mykola; Rizo, Zakhar; Polishchuk, Alla; Kress, Denis; Kuttiubaev, Aidar (Fundamental Research and Application of Physical Science, 2023)
Prof. L.I. Baron identified five forms of destruction during uniaxial compression of samples of regular geometry of rocks including truncated wedge, wedge, diagonal, longitudinal, and explosive forms. All of them are commonly characterized by the destruction of samples in their central parts showing two or more cracks, while the trajectories of crack development align with the corner points of the samples. Recently, was unexpectedly discovered a spall fracture in the form of a single crack emerged from the side wall of the specimen and propagating into it under uniaxial compression. Based on the discovery, the method for creating stress-strain diagrams for high rock samples was developed using four rock properties such as rock shear resistance limit, contact friction ratio, internal friction ratio, and modulus of elasticity. The stress-strain diagram of the spall fracture of high samples is described by a descending curve, which is typical for the diagrams of fracture created by two adjacent cracks of regular geometry samples. The maximum stresses required for the destruction of high rock samples are lower than those for the destruction of regular geometry samples of rocks with similar physical and mechanical properties.Проф. Л.І. Барон виділив п'ять форм руйнування при одновісному стисканні зразків гірських порід правильної геометрії, включаючи усічено-клинову, клиноподібну, діагональну, поздовжню та вибухову форми. Усі вони зазвичай характеризуються руйнуванням у зразків центральної частини з наявністю двох і більше тріщин, у своїй траєкторії розвитку тріщин збігаються з кутовими точками зразків. Нещодавно несподівано було виявлено відкольний злам у вигляді одиночної тріщини, що виникла від бічної стінки зразка і поширювалася в неї при одновісному стисканні. На основі цього відкриття було розроблено метод побудови діаграм напруження-деформації для високих зразків порід з використанням чотирьох властивостей породи, таких як межа опору зсуву, коефіцієнт контактного тертя, коефіцієнт внутрішнього тертя та модуль пружності. Діаграма напруження-деформації відкольного руйнування високих зразків описується спадаючою кривою, що притаманно діаграмам руйнування, створюваних двома сусідніми тріщинами зразків правильної геометрії. Максимальне напруження, необхідне для руйнування високих зразків гірських порід, нижча, ніж для руйнування зразків гірських порід правильної геометрії з аналогічними фізико-механічними властивостями.
Форми відкольного руйнування високих зразків гірських порід при одновісному стисканні
Keywords: spall fracture; відкольне руйнування; geotechnical mechanics; геотехнічна механіка; shear resistance limit; межа опору зсуву; crack development; розвиток тріщин